Single Intense Microsecond Electric Pulse Induces Radiosensitization to Ionizing Radiation: Effects of Time Intervals Between Electric Pulse and Ionizing Irradiation - Rezaee, Zohre; Yadollahpour, Ali; Bayati, Vahid (Frontiers in Oncology, 2018)
Background and Objective: Recent studies have shown the potential of electroporation (EP) as a physical radiosensitizer for ionizing radiation (IR). The amount of sensitizing effect depends on some factors the most important of them is the time interval between the EP and IR. This experimental in vitro study aims to investigate the radiosensitizing effect of EP exposure prior to IR and also evaluate the effects of EP-IR time intervals on the amount of radiosensitizing effects. Methods: Chinese hamster ovary (CHO) cell lines were cultured in vitro. The cells were divided into 10 groups including one untreated or control group, IR, and EP treatment alone groups, and seven combined EP-IR groups with 10, 20, 30, 40, 50, 60, and 70 min intervals. The dose enhancement factors (DEFs) for 6 MV X-rays IR were comparatively investigated between the groups using MTT assay. Results: The EP significantly induced radiosensitizing effect and its amount depends on the time intervals. The viability rate of the cells in the combined EP-IR treatment groups for intervals of 10, 20, 30, 40, and 50 min was significantly lower than the IR alone group. The highest DEF (1.18) was observed 10 min time interval between EP and IR. Conclusion: The radiosensitizing effects of EP persist long enough, 10-50 min, which allows safe application of EP as a radiosensitizer before IR in clinical setting.